Gender Difference in Pain Management Among Adult Cancer Patients in Saudi Arabia: A Cross-Sectional Assessment - Alodhayani, Abdulaziz; Almutairi, Khalid M.; Vinluan, Jason M.; Alsadhan, Norah; Almigbal, Turky H.; Alonazi, Wadi B.; Batais, Mohammed Ali (Frontiers in Psychology, 2021)
Objective: To compare gender differences in pain management among adult cancer patients in Saudi Arabia and to explore the predictors associated with attitudinal barriers of cancer patients to pain management. Methods: A descriptive cross-sectional study was conducted among 325 cancer patients from tertiary hospitals in Saudi Arabia. Result: Of the total participants, 67.4% were females (N=219) and 32.6% were males (N=106). The overall mean scores of the attitudinal barriers’ questionnaire were 49.51 ± 13.73 in males and 54.80 ± 22.53 in females. The analysis shows significant differences in scores in subscale of tolerance (male = 7.48 ± 2.37), (female = 8.41 ± 3.01), (p = 0.003) and fear of distracting in course of treatment in (male = 6.55 ± 1.34), (female = 7.15 ± 2.63) (p = 0.008). Female patients reported a moderate to severe level of pain than males (Worst Pain in last week” of 7.07 ± 1.50, Worst Pain in last week” of 5.84 ± 2.65, respectively). Splitting by gender that in male cancer patients the significant predictor for physiology effect domains includes age, marital status, employment status, monthly income, cancer type and presence of comorbid disease (p<0.050). Age was a significant predictor of the domains of fatalism, communication and harmful effects (p<0.050) among female cancer patients. Conclusion: The present study revealed significant differences between males and females with the attitudinal barriers to cancer pain management. Managing pain requires the involvement of all methods in a comprehensive manner, thus unalleviated pain influence the patients psychological or cognitive aspect.